Immunomodulatory effects of selected cyanobacterial peptides in vitro - Moosova, Zdena; Hrouzek, Pavel; Kapuscik, Aleksandra; Blaha, Ludek; Adamovsky, Ondrej (Toxicon, 2018)
Cyanobacteria produce many biologically active metabolites synthesized via nonribosomal synthetic pathways such as cyclic microcystins (MCs) and linear aeruginosins (Aers). The present study aimed to investigate the effects of different MC variants and the newly isolated aerugenosin Aer-865 on macrophages, which represent one of the key effector cells within the innate immune responses. Specifically, our study included RAW 264.7 macrophage activation associated with production of cytotoxic and cytostatic nitric oxide (NO) as well as pro-inflammatory mediators like tumor necrosis factor α (TNFα) and interleukin 6 (IL-6). From the compounds investigated, commonly occurring MC variants (-RR, -YR) and Aer-865 had no significant effects within the non-cytotoxic concentrations tested, i.e. 0.001-1 μM for MCs and 0.1-50 μM for Aer-865. In contrast to known immunoactive MC-LR, the negligible immunomodulatory potential of tested MC congeners could be related to their differences in structure. The knowledge of MC structure-specific activities contributes to the understanding of complex toxicity of different MC variants and most importantly their mixtures. This study is one of the first study that evaluate the effect of larger set of cyanobacterial peptides on macrophages and compare their immunomodulatory potential.
Keywords: mikrocystiny; RAW 264.7 buňky; Immunomodulation; Microcystins; Cyanobacteria; RAW 264.7 Cells; Cyanotoxins; imunomodulace; toxiny kmene Cyanobacteria; Innate immunity; Bacteriocins; bakteriociny; Cyanobacteria Toxins; Marine Toxins; Animals; zvířata; makrofágy; myši; Bacterial Toxins; Mice; Macrophages; mořské toxiny; bakteriální toxiny